Overview of the Activities on Heavy Duty Diesel Engines Waste Heat Recovery with Organic Rankine Cycles (ORC) in the Frame of the ECCO-MATE EU FP7 Project. (September 2017) - Lion, Simone; Vlaskos, Ioannis; Rouaud, Cedric; Taccani, Rodolfo
Abstract: The ECCO-MATE Project is a European Union funded project aimed to develop a synergistic framework for cutting edge research on novel engine technologies for higher energy efficiency and lower emissions. The project partners, Ricardo plc, an engineering consulting company, and the University of Trieste, focus the research attention on waste heat recovery systems, such as Organic Rankine Cycles (ORC), which are gaining increasing interest by engine manufacturers, vehicles and ships fleet operators, because of their potential for further increasing engine efficiency and decreasing fuel consumption. In particular, in the frame of the developed research activity, the 1-D Ricardo engine simulation software WAVE has been used in order to assess novel engine concepts, both in the commercial vehicles and marine sectors. A combined engine-ORC system First and Second Law of Thermodynamics analysis has been proposed in order to study where system inefficiencies are concentrated and propose improvements, with particular focus on commercial vehicle heavy duty diesel engines. A thermo-economic analysis has been also considered. Furthermore, in collaboration with the project partners National Technical University of Athens (NTUA) and Winterthur Gas & Diesel (WinGD), an innovative low pressure Exhaust Gas Recirculation (EGR) configuration for low speed 2-stroke ship propulsion units has also been studied with the aim of reducing NOx in order to meet IMO Tier III emissions limits. ORC systems are, in this application also, a promising technology that can be used, in synergy with emission reduction systems, to recover, in particular, low temperature heat sources such as engine coolant and scavenging air, always with the aim of improving overall system efficiency while respecting new stringent emission reduction targets. The first results of the research activity show that a fuel consumption improvement up to 10% could be achieved both for commercial vehicles off-highway applications and in the marine sector, depending on the type of ORC and waste heat recovery architecture chosen and the engine considered.